2017
DOI: 10.1093/mnrasl/slx094
|View full text |Cite
|
Sign up to set email alerts
|

Stellar envelopes of globular clusters embedded in dark mini-haloes

Abstract: We show that hard encounters in the central regions of globular clusters embedded in dark matter (DM) haloes necessarily lead to the formation of gravitationally-bound stellar envelopes that extend far beyond the nominal tidal radius of the system. Using statistical arguments and numerical techniques we derive the equilibrium distribution function of stars ejected from the centre of a non-divergent spherical potential. Independently of the velocity distribution with which stars are ejected, GC envelopes have d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 36 publications
4
58
0
Order By: Relevance
“…Thus, the cosmological star formation would be processed, in part, in structures similar to globular clusters. The presence of non-baryonic dark matter in globular clusters has recently been discussed by Sollima et al (2016) and Peñarrubia et al (2017). Our work shows consistency with the results and analyses of these authors.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the cosmological star formation would be processed, in part, in structures similar to globular clusters. The presence of non-baryonic dark matter in globular clusters has recently been discussed by Sollima et al (2016) and Peñarrubia et al (2017). Our work shows consistency with the results and analyses of these authors.…”
Section: Discussionsupporting
confidence: 93%
“…Other simulations show that tidal effects of the host galaxy can remove a large amount of the original DM inside GCs (Mashchenko & Sills 2005b). More recently, Peñarrubia et al (2017) showed that stars ejected due to hard encounters in the central region of GCs embedded in a DM halo generate an envelope of gravitationally bounded stars. Supporting this model, so-called extratidal stars have been observed in many GCs of the MW (e.g., Carballo-Bello et al 2012, 2018 and the Andromeda galaxy .…”
Section: Dm In Gcsmentioning
confidence: 99%
“…Leaman et al 2013;Massari et al 2019); yet it is still unclear whether they originated in the early universe within dark matter mini-halos or simply as gravitationally bound clouds (e.g. Peebles 1984;Peñarrubia et al 2017).…”
Section: Introductionmentioning
confidence: 99%